HISTORIOGRAPHY OF PERSONAL LIBRARIES OF LITUANIAN WRITERS - LIEPAITĖ, INGA (Knygotyra, 2015)
Personal libraries of writers may be one of possible relevant research topics of book science. The first research works of memorial libraries of Lithuanian writers that were delineated purposefully and structurally appeared in the second half of the 70-iese of the past century. Their initiator and author was the book researcher professor Vladas Žukas. He published the investigation results of studying the personal libraries of writers Antanas Vienuolis-Žukauskas (1977), Petras Cvirka (1978), Mikalojus Akelaitis (1983), Sofija Kymantaitė-Čiurlionienė (1983), Maironis (1987) and Andrius Vištelis (1987). The interest was also shown in the personal libraries of writers Jonas Biliūnas, Vincas Krėvė, Vincas Mykolaitis-Putinas, Bronius Pranskus, Salomėja Nėris, Balys Sruoga, Antanas Venclova and others. Supervised by prof. V. Žukas, quite a number of Vilnius University students defended their diploma theses in the above mentioned area, naturally, more or less reflecting the attitude of the research tutor. The graduates investigated the personal libraries of P. Cvirka (1975), B. Sruoga (1977), Kostas Kubilinskas (1977), S. Kymantaitė-Čiurlionienė (1977), Kazys Boruta (1978), A. Venclova (1980), Juozas Tumas-Vaižgantas (1982), V. Krėvė (1984) and Ieva Simonaitytė (1989). In the said period they used methodological experience of the Soviet Russia, where, starting with the 50-ies, the libraries of famous Russian writers of 18–20th centuries were investigated, numerous articles and catalogs were written, discussion were held on the issues of compilation methodology. This article aims to reveal and characterize scientific or other professional evaluations of personal libraries of Lithuanian writers as well as to review the experience gained during over half century and the work cultivated in the area of such activities. The basis for the research consists of published and unpublished historiographic material and other sources allowing to get a deeper and broader understanding of events. Historiography of the subject matter may be divided into two stages: 1) until 1990 and 2) after 1990. The first stage was rather strenuous and productive; in a short time much has been achieved. However, after regaining the independence of Lithuania, it is obvious that scientific research in personal libraries of Lithuanian writers has noticeably slowed down. Sometimes one or another writer‘s personal library in certain cases gains more attention from workers of memory institutions than from representatives of book science, librarianship or literature studies. Therefore it is imperative that potentialities of continuing the initiated tasks and compiling catalogs of memorial libraries of Lithuanian writers are considered.